Code-Switching in the Frequently Used English Vocabularies among College Students of Non-Native Speaker - Intan Roshalia; Yudi Basuki (Universitas PGRI Madiun, 2022)
Code-switching is a common linguistic phenomenon that occurs because of the need for two or more languages when communicating directly in general or specific expressions in the world’s multilingual society. The research aimed to find out and to describe code-switching in the frequently used English vocabularies among college students of non-native speaker. The research used qualitative focuses on phenomenological research. The research involved the first until third-year students of the English Language Education Department of STKIP PGRI Trenggalek in the 2021/2022 academic year as the subject. The research instruments were questionnaires and documentation was analyzed using Likert scale and qualitative descriptive way. Research findings show students mostly agree with the use of code-switching in their daily communication and their social media such as WhatsApp, Facebook, and Instagram. From 95 vocabularies presented in the questionnaire, 85 vocabularies are the most frequently used in students’ daily communication. Moreover, given the findings, discussions, and conclusion elaborated above, it is suggested for college students, lecturers, college and next researchers may find benefits in this research.